2012
DOI: 10.1515/htmp-2012-0104
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Pure Solid CaS with Ar-O2 Gas Mixture

Abstract: Synopsis:Oxidation behavior of CaS in oxidizing atmo sphere has been investigated for the regeneration process of desulfurization slag by oxidation. The temperature range of oxidation of CaS reagent with Ar21%O 2 gas was 973 to 1423 K. The weight gain was observed in the lower temperature range and reached at the maximum value at 1173 K while weight gain turned to decrease when the reac tion temperature was higher than 1173 K. It was clarified that CaS was oxidized to CaSO 4 under 1173 K or to CaO over 1373 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
3
2
0
Order By: Relevance
“…It can be seen from Figure 15a that gas flow rate has little influence on sulfur removal in slag. This is the same as the pure CaS oxidation rate independent of gas flow rate reported by Kobayashi et al [21]. The surface area of the slag contained in the Al 2 O 3 crucible boats is approximately 200% larger compared to the slag in the Al 2 O 3 crucibles.…”
Section: Removal Rate Of Sulfur From Slagsupporting
confidence: 85%
See 2 more Smart Citations
“…It can be seen from Figure 15a that gas flow rate has little influence on sulfur removal in slag. This is the same as the pure CaS oxidation rate independent of gas flow rate reported by Kobayashi et al [21]. The surface area of the slag contained in the Al 2 O 3 crucible boats is approximately 200% larger compared to the slag in the Al 2 O 3 crucibles.…”
Section: Removal Rate Of Sulfur From Slagsupporting
confidence: 85%
“…It can be seen from Figure 15a that gas flow rate has little influence on sulfur removal in slag. This is the same as the pure CaS oxidation rate independent of gas flow rate reported by Kobayashi et al [21]. The surface area Therefore, at high oxygen pressure (P O 2 ≥ 0.20 bar), the limiting step of the sulfur oxidation process in slag is S 2− diffusion control in the liquid phase.…”
Section: Removal Rate Of Sulfur From Slagsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been shown earlier that CaS can be oxidized into CaO at elevated temperatures [1,2]. The sulfur forms SO 2 gas.…”
Section: Introductionmentioning
confidence: 92%
“…The increase of the degree of sulfur removal with increasing oxygen partial pressure strongly suggests that the formation of sulfate in the slag is avoided with the present experimental conditions. Kobayashi et al concluded that CaS is oxidized to CaO above 1223 K in air [1]. Pelton et al also concluded that no appreciable amount of sulfate or oxy-sulfide species was formed within the bulk slag at any time [4].…”
Section: Sulfur Removal Of Liquid Slagmentioning
confidence: 99%